“Dying alone and being eaten”: dog scavenging on the remains of an elderly animal hoarder-a case report - Kmetiuk, Louise Bach; Maiorka, Paulo César; Beck, Alan M.; Biondo, Alexander Welker (Frontiers in Veterinary Science, 2023)
Animal hoarding and human consumption by dogs have been important but often understudied aspects of the human-animal bond that can be addressed within a One Health framework. No scientific report has focused on dog scavenging on animal hoarders to date, despite isolated reports of dog scavenging on human remains, mostly due to starvation and the phenomenon has been approached as a confounding factor for human forensics. In 2014, the Animal Protection Department of Curitiba City was called to rescue and handle ten small dogs after scavenging for a week on the human remains of their elderly owner, a potential animal hoarder. At inspection, three dead dogs in early putrefaction were also found in the household. Human autopsy revealed body putrefaction and lack of soft organs. Along with the dental arch, DNA testing was performed on the remains for official deceased identification. Due to potential public health risks of aggression towards physically fragile human beings or control of transmitting zoonotic diseases, all ten dogs were euthanized. Subsequent investigations by the crime scene police, homicide police and autopsy services were unable to establish or rule out natural death, criminal or suicidal poisoning, zoonotic disease (rabies), fatal dog attack or fatal accidental trauma. A general protocol has been proposed for future approach of dog scavenging and suspicious killing of animal hoarders, as well an assessment for potential adoption or euthanasia of animals owned by hoarders in these circumstances.